Exosomal lncRNA UCA1 Derived From Pancreatic Stellate Cells Promotes Gemcitabine Resistance in Pancreatic Cancer via the SOCS3/EZH2 Axis - Chi, Yuan; Xin, He; Liu, Zhaoyu (Frontiers in Oncology, 2021)
Objective: Pancreatic cancer is associated with poor prognosis and dismal survival rates. This study aims to investigate roles of lncRNA UCA1-loaded exosomes secreted by pancreatic stellate cells (PSCs) in Gemcitabine (Gem) resistance of pancreatic cancer under hypoxia, which involves the methylation of SOCS3 and EZH2 recruitment. Methods: The exosomes were isolated from PSCs and hypoxic PSCs (HPSCs), and co-cultured with pancreatic cancer cells transduced with manipulated lncRNA UCA1, EZH2, and SOCS3. The interaction among lncRNA UCA1, EZH2, and SOCS3 was characterized by RIP and ChIP assays. Next, MTT assay, flow cytometry and TUNEL staining and Transwell assay were used to detect cell viability, apoptosis, invasion, and migration. Gem-resistant pancreatic cancer cell line (GemMIA-R3) was established, which was applied in a mouse xenograft model of pancreatic cancer, with MTT assay to determine Gem sensitivity. Results: LncRNA UCA1 was highly expressed, while SOCS3 was poorly expressed in pancreatic cancer tissues. Hypoxia induced activation of PSCs and promoted release of exosomes. LncRNA UCA1 delivered by hypoxic PSC-derived exosomes (HPSC-EXO) regulated histone methylation level in SOCS3 gene region through recruitment of EZH2. In vitro and in vivo experimental results confirmed that lncRNA UCA1-loaded HPSC-EXO promoted malignant phenotypes, inhibited apoptosis, and promoted Gem resistance of pancreatic cancer cells as well as tumorigenesis in mice. Conclusion: Under hypoxic conditions, exosomes secreted by hypoxia-induced PSCs deliver lncRNA UCA1 into pancreatic cancer cells, where lncRNA UCA1 recruits EZH2 and regulates histone methylation level in SOCS3 gene region, thereby augmenting pancreatic cancer resistance to Gem.